3D Printing of Mechanically Elastic, Self‐Adhesive, and Biocompatible Organohydrogels for Wearable and Breathable Strain Sensors. Issue 5 (2nd December 2022) - Guo, Binbin; Zhong, Yukun; Song, Xiaoxia; Chen, Xiaoteng; Zhou, Peng; Zhao, Fuxin; Bai, Jiaming
Abstract: Organohydrogel‐based strain sensors have gained increasing attention in the fields of real‐time healthcare and motion detection due to their excellent flexibility, stretchability, and skin‐like compliance. However, the fundamental attributes, such as mechanical elasticity, self‐adhesiveness, and biocompatibility, are challenging to be simultaneously obtained in organohydrogels, limiting their applications in wearable electronics. Additionally, traditional organohydrogels need to be fixed to the surface of the human skin and suffer from inferior breathability, resulting in complicated operations and severe uncomfortableness, respectively. Herein, a multifunctional organohydrogel is designed for wearable strain sensor by a facile digital light processing (DLP) 3D printing technology. By rationally tailoring the chemical (poly( N ‐acryloylmorpholine)/poly(ethylene glycol) diacrylate) and physical (poly( N ‐acryloylmorpholine)/poly(ethylene glycol) diacrylate and glycerin/water) cross‐linking networks, the organohydrogel exhibits promising water absorption/retention, high stretchability, impressive elasticity, and promising fatigue resistance. Additionally, good ionic conductivity, inherent self‐adhesiveness, and biocompatibility are simultaneously achieved. On the basis of the multifunctionalities, 3D multihole organohydrogels are designated as wearable and breathable strain sensors, facilitating the manipulation without any fixation and increasing the wear comfortableness. It is believed that 3D printed multihole organohydrogels show great potential in wearable flexible electronics. Abstract : Chemically and physically cross‐linked networks are tailored to construct a multifunctional organohydrogel, simultaneously realizing promising water absorption/retention, high stretchability, impressive elasticity, fatigue resistance, self‐adhesiveness, and biocompatibility. Taking advantage of these merits, 3D multihole organohydrogels are printed and designated as wearable and breathable strain sensors, facilitating the manipulation without any fixation and increasing the wear comfortableness.